2014
DOI: 10.1186/1746-160x-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation pattern and tissue integration of native and cross-linked porcine collagen soft tissue augmentation matrices – an experimental study in the rat

Abstract: IntroductionWithin the last decades, collagen types I and III have been established as a sufficient biomaterial for GBR and GTR procedures. They might also be an adequate matrix for soft tissue augmentations. However, collagen materials differ significantly regarding resorption time, biodegradation pattern and the invasion of inflammatory cells.The aim of the present study was to compare the biodegradation and tissue integration of native, differently processed and cross-linked collagen scaffolds in rats.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
107
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 33 publications
9
107
0
4
Order By: Relevance
“…In an animal model, the rough and porous collagen structure was shown to serve as a scaffold for ingrowing blood vessels and cells, enabling revascularization of the matrix and its integration into the surrounding tissue with progressive complete remodeling. [91011] This property may explain the good integration, demonstrated by histological findings, observed in this study. Biopsy samples from all sites showed evidence of angiogenesis and mature connective tissue covered by keratinized epithelium, with clinical gains in mucosal thickness ranging from 0.7 to 1.5 mm.…”
Section: Discussionsupporting
confidence: 60%
“…In an animal model, the rough and porous collagen structure was shown to serve as a scaffold for ingrowing blood vessels and cells, enabling revascularization of the matrix and its integration into the surrounding tissue with progressive complete remodeling. [91011] This property may explain the good integration, demonstrated by histological findings, observed in this study. Biopsy samples from all sites showed evidence of angiogenesis and mature connective tissue covered by keratinized epithelium, with clinical gains in mucosal thickness ranging from 0.7 to 1.5 mm.…”
Section: Discussionsupporting
confidence: 60%
“…However, Rothamel et al found no difference in degradation pattern between using NCCM and CCM after 12 weeks in a subcutaneous model (Rothamel et al 2014). Those authors reported that the faster degradation of thermally produced CCM might result from combining collagen types I and III in a porous structure.…”
Section: Discussionmentioning
confidence: 96%
“…Chemically produced CCM showed improved mechanical properties, but it induced severe inflammatory reactions. Another recent study found that dehydrothermally produced CCM showed comparable biodegradation pattern without inducing a foreign-body reaction (Rothamel et al 2014). …”
Section: Discussionmentioning
confidence: 97%
“…[21][22][23][24][25] Clinical studies have proven that tissue integration is satisfactory and unproblematic, with complete CM remodeling and biodegradation. 8,9 These promising results can be confirmed by the functional and esthetic outcomes observed in this study.…”
mentioning
confidence: 99%